English Perceptions and Representations of Venetian Chromatic Variations - Anne GEOFFROY (E-REA)
While Newton was the first to split white light using a triangular prism in 1671, thus putting an end to the linear system of the Aristotelian chromatic scale, previous experiments using the prism as an optical instrument had been made a hundred years before by the Venetian Filipo Mocenigo, Archbishop of Nicosia. These attempts at understanding colours need to be linked to the uniqueness of the Venetian environment and to the quality of light in the lagoon where refraction is a daily phenomenon. Although Venetian colours have traditionally been associated to painting, they also belong to the texture of the city itself as exemplified in marbles and mosaics. As early as the 15th century, the city boasted a flourishing industry of colour relying on trades such as, among others, dyers, glassmakers, tailors, or pigment sellers (i.e. vendecolori).This paper explores the material, cultural and linguistic influence of Venice on early modern England, focusing more precisely on glass, dyes and pigments. The perception and representation of the Venetian palette will be analysed through various sources, so as to shed light on the way colours informed the imaginative construct of the city while revealing the British travellers’ ability or inability to be responsive to Venice’s ubiquitous polychromy.